Anti-Hyperglycemic and in Vivo Antioxidant Activities of Aqueous Extract of Blighia sapida Stem Bark in Alloxan-Induced Diabetic Rats (Global Journal of Medical Research, 2017)
Blighiasapida is a plant belonging to the family of Sapindaceae. This study is aimed at evaluating the hypoglycemic and possible in vivo antioxidant activities of the aqueous extract of the stem bark of the plant for 21 days in alloxan-induced diabetic rats. Administration of the extract at 100mg/kg body weight significantly (P
Keywords: blighiasapida; diabetes; antioxidant enzymes; epidemic; biomolecules